PENGEMBANGAN MODUL AJAR PAI BERDIFERENSIASI UNTUK MENGUATKAN PEACE EDUCATION DAN MULTIPLE INTELLIGENCE SISWA SEKOLAH DASAR - Isna Nurul Inayati, Sutomo (PRODI PAI FIK UNIRA MALANG, 2024)
This research was conducted as an alternative to overcome learning loss that occurred after the Covid-19 pandemic and the lack of availability of differentiated PAI learning modules in Madrasahs which resulted in low learning outcomes and weak student character. So to overcome this problem, researchers feel the need to develop a differentiated PAI Teaching Module so that learning activities, intelligence levels and character quality of students increase. The type of research used is Research and Development (R&D) with the ASSURE model, with several stages, namely: a) analyze learners, b) state objectives, c) select methods, media, and materials, d) utilize materials, e) require learners participation, f) evaluate and revise. The trial of this research product was conducted at SDN 01 Palaan, Malang Regency. The research instrument used a questionnaire sheet and data analysis used descriptive statistical analysis. The results of this study indicate that the development of a differentiated PAI teaching module in the category is feasible to use and efficient to strengthen the values ​​of peace education and multiple intelligence of elementary school students